Analysis of global liquidity in the context of financial indicators - Chaban, Andrii (Актуальні питання економічних наук, 2025)
The relevance of the study stems from significant transformations in the global financial environment, driven by the monetary decisions of central banks in leading countries, changes in financing sources, the expansion of the non-banking sector, and the proliferation of digital financial instruments. In these conditions, traditional indicators of the money supply lose their analytical capacity, which complicates the timely identification of risks to financial stability. The purpose of this article is to identify the mechanisms of global liquidity formation and to clarify its impact on the financial stability of economies with an open financial architecture, through an analysis of the relationship with key macroeconomic indicators that reflect the dynamics of global financial markets. The research methodology is based on a systematic analysis of the processes of global liquidity formation, employing a structural-functional approach, comparative analysis, and generalization methods, which enable tracing the relationships between indicators of global liquidity and changes in monetary, foreign exchange, and debt policies. Results. The limitations of traditional monetary aggregates (M2, M3) in assessing transnational liquidity are revealed and the feasibility of using GLI indices as more sensitive indicators is substantiated. It has been demonstrated that fluctuations in global liquidity have a significant impact on interest rates, exchange rates, and the structure of debt obligations, particularly in countries with an open financial architecture. It is established that the policy of central banks shapes not only the volume of liquid resources, but also their transmission channels, causing asymmetries in access to financing. The scientific novelty of the study lies in the structured generalization of factors that determine the effectiveness of global liquidity, taking into account regulatory restrictions (Basel III, CCAR) and the influence of non-bank financial institutions. A classification of indicators is proposed based on the source of liquidity formation and the degree of coverage of transnational flows. Conclusions. The dual nature of the impact of global liquidity is substantiated: its excess generates financial imbalances and speculative «bubbles», while its deficit increases the vulnerability of markets and limits lending. Prospects for further research are identified as an in-depth analysis of the role of the non-banking sector, central bank digital currencies, and decentralized financial platforms in transforming global liquidity distribution channels.